Prediksi Jumlah Pengunjung Perpustakaan Daerah Kabupaten Batang dengan Menggunakan Metode Fuzzy Time Series Chen-Hsu - Rahmawati Rahmawati; M. Rafly Ramaesa Putra; Fitriani Muttakin (Journal of Mathematics UNP, 2023)
The Batang Regency Library is one of the places that is often visited by the local community. Analysis of library visiting patterns and predicting the number of visitors is very important to do, because this is the basis for planning effective policies for stakeholders to make librarians feel comfortable. The purpose of this study was to predict the number of visitors to the Batang Regency Regional Library in 2023. The Chen-Hsu Fuzzy Time Series method was used in this study because it provides a MAPE value which can provide easier proof of accuracy compared to other methods. The results showed that visitors to the Batang Regency regional library from 2018-2022, there was a decrease in 2021 to 2022, and according to forecasting results using the Fuzzy Time Series Chen-Hsu method, visitors to the Batang Regency Regional library did not change from the previous year and had an average average MAPE 15.56%, so the level of accuracy is good.